2012
DOI: 10.1189/jlb.0512244
|View full text |Cite
|
Sign up to set email alerts
|

Effects of IFN-γ on intracellular trafficking and activity of macrophage NADPH oxidase flavocytochrome b558

Abstract: IFNγ regulates trafficking and synthesis of flavocytochrome b558, suggesting a role to control superoxide production in macrophages. Flavocytochrome b558, the catalytic core of the phagocyte NADPH oxidase (NOX2), mediates electron transfer from NADPH to molecular oxygen to generate superoxide, the precursor of highly ROS for host defense. Flavocytochrome b558 is an integral membrane heterodimer consisting of a large glycosylated subunit, gp91phox, and a smaller subunit, p22phox. We recently show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 55 publications
(82 reference statements)
1
33
0
Order By: Relevance
“…; Casbon et al. ). We assessed subcellular distribution of NOX2 in WT and matched C1KO macrophages (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…; Casbon et al. ). We assessed subcellular distribution of NOX2 in WT and matched C1KO macrophages (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…To demonstrate further the involvement of NADPH oxidase in IFNγ-induced ROS production, double immunocytochemical staining showed translocation of p47phox from cytoplasm to membrane and co-localized with the gp91phox after treating cells with IFNγ (Figure 8). In a study with macrophages, IFNγ was shown to activate NADPH oxidase through increase in intracellular trafficking and expression of gp91phox [40]. …”
Section: Discussionmentioning
confidence: 99%
“…IFN-γ can regulate NAPDH oxidase activity in different cell types 8 . O 2 - is rapidly converted to H 2 O 2 by spontaneous and enzymatic dismutation.…”
mentioning
confidence: 99%